2010
DOI: 10.1007/s10943-010-9419-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spirituality and Religion on Outcomes in Patients with Chronic Heart Failure

Abstract: Heart failure (HF) is a chronic progressive disease with marked morbidity and mortality. Patients enduring this condition suffer from fluctuations in symptom burden such as fatigue, shortness of breath, chest pain, sexual dysfunction, dramatic changes in body image and depression. As physicians, we often ask patients to trust in our ability to ameliorate their symptoms, but oftentimes we do not hold all of the answers, and our best efforts are only modestly effective. The suffering endured by these individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 42 publications
3
32
0
3
Order By: Relevance
“…The benefits include (1) evokes comforting emotions and feelings; (2) offers strength, empowerment, and control; (3) eases the emotional burden of the illness; (4) offers social support and sense of belonging; (5) offers spiritual support through a personal relationship with God; (6) facilitates meaning and acceptance of the illness; (7) helps preserve health; (8) relieves the fear of death and uncertainty of death; and (9) facilitates self-acceptance and reduces self-blame. This is consistent with the findings of Naghi et al (2012) findings that spirituality is used as a coping mechanism for clients with heart failure. Thus, it seems that occupational therapist and students should have insight about the importance of spirituality in clients' life.…”
Section: Benefits Of Spirituality To Clientssupporting
confidence: 93%
See 1 more Smart Citation
“…The benefits include (1) evokes comforting emotions and feelings; (2) offers strength, empowerment, and control; (3) eases the emotional burden of the illness; (4) offers social support and sense of belonging; (5) offers spiritual support through a personal relationship with God; (6) facilitates meaning and acceptance of the illness; (7) helps preserve health; (8) relieves the fear of death and uncertainty of death; and (9) facilitates self-acceptance and reduces self-blame. This is consistent with the findings of Naghi et al (2012) findings that spirituality is used as a coping mechanism for clients with heart failure. Thus, it seems that occupational therapist and students should have insight about the importance of spirituality in clients' life.…”
Section: Benefits Of Spirituality To Clientssupporting
confidence: 93%
“…There are benefits for students to learn about spirituality and clients benefit from spirituality when they experience challenges and illnesses (Meredith et al 2012;Naghi et al 2012). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Such behaviors are termed as positive activity interventions and include exercises such as doing acts of kindness, counting one's blessings, thinking about good things, writing letters of gratitude, and meditating on positive feelings toward others (Layous et al, 2011). Many of the attributes of positive psychology also form the common core elements of most spiritual practices, and the report by Mills et al supports and extends prior studies linking spiritual well-being to heart health (Naghi, Philip, Phan, Cleenewerck, & Schwarz, 2012). However, because a cross-sectional study cannot determine causality, the enthusiasm for the findings by Mills et al has to be tempered till they are confirmed in larger controlled trials.…”
mentioning
confidence: 79%
“…This fact has recently been recognized as a priority in palliative care practice and research (Selman et al 2014). Spiritual distress has been observed in palliative patients (Gielen et al 2017) in addition to patients with cancer (Caldeira et al 2014), heart failure (Naghi et al 2012;Strada et al 2013), respiratory insufficiency (Strada et al 2013), kidney failure (De Cássia Lopes Chaves et al 2010), and mental illness (Yang et al 2012). Cancer patients may have spiritual distress at the diagnosis phase, at recurrence, and later in the terminal phase (Murray et al 2005).…”
Section: Spiritual Distressmentioning
confidence: 99%